Access to domestic water supply and women empowerment - Experience from Chhattisgarh and Madhya Pradesh - Devi, Hijam Eskoni; Purandare, Vaibhav (2014)
Poor access to water burdens women most as they are primarily responsible for its use and management in the household. In the absence of domestic water connection, women often trudge long distances, stand for hours every day to fetch water from alternative external sources, wasting time and energy which could otherwise be used in pursuit of productive activities. Carrying water over long distances has a negative impact on health. This study examines policy interventions of the Government of Chhattisgarh and Jabalpur Municipal Corporation, Madhya Pradesh to improve access to water by providing domestic water connections to the urban poor. The policies and interventions resulted in improved socio-economic status,improved public health and contributed to women empowerment-their ability to take personal and family decisions. - Reproduced.
Keywords: Water supply; Women